(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This study evaluated breakfast flaked samples produced from rice and kidney bean flour blends. The rice grains were sorted, winnowed, washed, soaked, drained, dried, milled, and sieved, whereas, the kidney bean seeds were sorted, cleaned, boiled, drained, dehulled, washed, dried, milled, and sieved. The rice and kidney bean flours were blended in the ratio of 100:0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80 and 10:90 of rice and kidney bean. The blended flours were weighed, mixed, heated, aged, cut, toasted, cooled and packaged to obtain the flaked samples. The three best samples from the sensory evaluation of breakfast flake samples (60:40, 30:70, 10:90) were analysed for proximate composition using standard methods. The data obtained were statistically analysed using SPSS and means were separated at 0.05 level of significance. The sensory properties of the breakfast flake samples ranged from 6.07 to 7.53 for colour, 5.67 to 7.80 for taste, 6.20 to 7.13 for texture, 6.20 to 7.00 for flavour and 5.27 to 6.87 for overall acceptability. The breakfast flake samples produced were all acceptable, although sample A (60:40) was preferred most in terms of overall acceptability scores of 6.87±0.73. The results of the proximate composition of the samples showed that moisture ranged from 3.35 to 11.77%, protein 13.95 to 20.61%, ash 1.99 to 3.25%, fibre 1.66 to 4.67%, lipid 6.01 to 6.08% and carbohydrate 53.69 to 69.91%, respectively. It was observed, therefore, that the blends of the rice and kidney bean flour in breakfast flakes making should not exceed 50% of kidney bean flour substitution.